2017
DOI: 10.24043/isj.38
|View full text |Cite
|
Sign up to set email alerts
|

Yujiale fishing tourism and island development in Changshan Archipelago, Changdao, China

Abstract: Tourism has long been one of the driving forces of island development, but may impose serious impacts on their physical and social composition and on island communities. Yujiale has been developed recently on many islands of China. It is a form of tourism through which households earn money by sharing fishing culture and products in the distinctive natural and cultural context of islands. This research assesses the provision of Yujiale services and products by fishing families of Digou village, Changdao Island… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The social point of view for island tourism development has provided evidence on the influence of tourism on the local community"s behavior and their social structure (Andaria et al, 2013). The small islands in China have established an evidence for the other island based destinations as they earn money through sharing their fishing cultures as well as the products produced by the locals transfer an idea of impact of tourism development on the physical and social structure of the island communities (Su et al, 2017). It is found that the tourism industry will impact the life of the local people in some way whether the level of exposure of the local culture which actually demand for enacting majority of the people with the direct economic activities (Diedrich and Aswani, 2016).…”
Section: Socio-cultural Impactmentioning
confidence: 99%
“…The social point of view for island tourism development has provided evidence on the influence of tourism on the local community"s behavior and their social structure (Andaria et al, 2013). The small islands in China have established an evidence for the other island based destinations as they earn money through sharing their fishing cultures as well as the products produced by the locals transfer an idea of impact of tourism development on the physical and social structure of the island communities (Su et al, 2017). It is found that the tourism industry will impact the life of the local people in some way whether the level of exposure of the local culture which actually demand for enacting majority of the people with the direct economic activities (Diedrich and Aswani, 2016).…”
Section: Socio-cultural Impactmentioning
confidence: 99%
“…Agritourism is perceived as offering greater potential to enhance the security and welfare of community members as compared to resort-based enclave tourism. Similarly, island communities in China view agritourism as increasing revenue and reinforcing island identity (Su et al, 2017). In this context, agritourism takes the form of sharing fishing culture and practices rather than landbased agriculture-capitalizing on the fisheries-based livelihoods of these island communities.…”
Section: Agritourism and Food Security: A Global Reviewmentioning
confidence: 99%
“…Impacts from this effectively unregulated fishery, if any, are not known, nor is information available on possible consequences of expanding the fishing because local monitoring of fish stocks has not occurred. This dearth of data is problematic when planning for more lucrative fishing-related livelihoods, such as through emulating approaches in other locations with China's Changshan Archipelago being an example (Su et al, 2017).…”
Section: Fishing and Huntingmentioning
confidence: 99%